1998
DOI: 10.1007/s004030050318
|View full text |Cite
|
Sign up to set email alerts
|

The monoclonal antibody AS02 recognizes a protein on human fibroblasts being highly homologous to Thy-1

Abstract: Recently, we described a novel fibroblast-restricted monoclonal antibody (mAb AS02) that recognizes a membrane-bound antigen. Characterization and isolation of the corresponding antigen showed that mAb AS02 recognized a protein on human fibroblasts that is highly homologous or identical to human Thy-1 antigen (CD90). Partial amino acid sequencing of the corresponding mAb AS02 antigen and comparison with known proteins revealed a 100% homology of the sequenced peptides to the human Thy-1 antigen. Cross-immunode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
104
1
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 84 publications
(107 citation statements)
references
References 13 publications
1
104
1
1
Order By: Relevance
“…Human Thy-1 is involved in the stimulation of MMP-9 release from neutrophils Since human Thy-1 is expressed on TNF-a-activated dermal microvascular EC and dermal fibroblasts [10,23], we studied whether neutrophils might interact with these cells in vivo. Double staining experiments using anti-CD15 antibody to detect neutrophils and an anti-Thy-1-antibody were performed in tissue sections of psoriatic skin lesions.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Human Thy-1 is involved in the stimulation of MMP-9 release from neutrophils Since human Thy-1 is expressed on TNF-a-activated dermal microvascular EC and dermal fibroblasts [10,23], we studied whether neutrophils might interact with these cells in vivo. Double staining experiments using anti-CD15 antibody to detect neutrophils and an anti-Thy-1-antibody were performed in tissue sections of psoriatic skin lesions.…”
Section: Resultsmentioning
confidence: 99%
“…Human Thy-1 is expressed on activated human dermal microvascular endothelial cells (HDMEC) and constitutively on dermal fibroblasts [23,28]. We demonstrated that Thy-1 Figure 7.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In humans, Thy-1 is constitutively expressed on fibroblasts, neuronal cells, a subpopulation of blood stem cells, and glomeruli cells [6,8,18,24]. In addition, activated microvascular ECs express Thy-1 [25].…”
Section: Discussionmentioning
confidence: 99%
“…Myofibroblasts express ␣-smooth muscle actin (␣-SMA), yet are negative for other smooth muscle markers such as smoothelin and desmin (16,17). These cells are also positive for the marker CD90, which in humans represents a useful fibroblast/ myofibroblast marker because, in humans, it is not expressed by T lymphocytes (35). The subepithelial, pericryptal fibroblastic sheath of the small intestine and colon is composed of intestinal myofibroblasts.…”
mentioning
confidence: 99%